Information Systems Management as an Academic Organizer of Madrasah Diniyah - Suharno, FA Suharno; Imraan, Mohd Imraan (The International Journal of Education Management and Sociology, 2024)
This research aims to reveal information systems management as the development of academic administration. To find out academic goals. This research uses a qualitative approach. Data collection techniques were carried out using interviews, observation, and documentation studies. Data analysis includes data reduction, data presentation, and conclusion, checking the validity of the findings by extending participation, and triangulation techniques of sources, theories, and methods. The conclusion is that the Head of the Madrasah, Academic and Curriculum Sector, and Human Resources and Services Sector. The results of the research findings show that: (1) The PSB activity process is still manual, the Santri registration business process is still conventional, the business process for determining homeroom teachers, the business process for determining learning schedules, the learning business process up to the Santri graduation process is carried out by Madrasah Diniyah Al -Hikam Bogor does not yet have written and documented standard procedures. (2) The Madrasah Diniyah Al-Hikam Bogor academic application/information system only coordinates the KMB Santri, both the Awaliyah program and the Wustha program. So information system management has not been fully carried out by the Madrasah. There needs to be strategic planning to build a system that can be integrated with other systems. To improve the quality of products and services, and also provide easy satisfaction for stakeholders.